984 Hospital Transmission of COVID-19 in Trauma Surgery. (4th May 2021) - Emerson, H
Abstract: Introduction: A single-site retrospective study identified a suspected cluster of hospital-acquired COVID-19 in trauma patients. The study aims to identify contributing factors in order to minimise future risk to patients and staff. Method: A single-site retrospective cohort study including all T&O patients who underwent surgery with confirmed peri-operative COVID-19 infection. The primary outcome was 30-day mortality. Exposures investigated included diagnostic timing and theatre designation. Results: 92% of participants were not tested pre-operatively. 75% met the criteria for hospital acquired COVID-19. Only 2 patients were operated on in designated COVID-19 theatres. Two lists accounted for 50% of the T&O COVID-positive patients. Remaining patients on both lists were discharged without further testing. Local 30-day mortality rate (25%) was in line with the findings of the international COVIDSurg Study (23.8%). No further COVID-positive T&O cases identified since the introduction of blanket admission swabbing. Conclusions: The majority of patients did not meet criteria for pre-operative testing. Thus, were not operated on in appropriately designated theatres despite unknown COVID status, increasing risk of cross-contamination. Complacency due to designation of "clean" and "dirty" wards, atypical presentation and bay nursing may have contributed to hospital transmission. Findings emphasise the importance of treating patients as COVID positive until proven otherwise.